The Samsung Medical Center (SMC) Knot: Surgical Technique and Demonstration With Teaching Modification - Christopher M. Gibbs, M.D.; Lucas G. Teske, M.D.; Benjamin R. Graves, M.D. (Arthroscopy Techniques)
Arthroscopic knot-tying is an important skill for any arthroscopist. Many types of knots have been proposed, each with various advantages and disadvantages. The Samsung Medical Center (SMC) knot is an arthroscopic sliding knot featuring a self-locking loop that has been demonstrated to have good knot security and a low-profile construct. This Technical Note and the accompanying video describe the technique for creating the SMC knot; furthermore, a modification to prevent premature locking of the knot to facilitate teaching the knot is demonstrated.